Improving Fine Motor Development Through Ronce Activities for Group B Children - Mailiza, Peni; Susanto, Rezi; Sarmita, Dian; Yenti, Yesni; Husni, Yunadil (Strata International Journal of Social Issues, 2024)
Integrated Anugrah Lingkitang River, Sangir District, South Solok Regency. Shows that the child's fine motor development condition is deficient. Based on this, the researchers implemented ronce activities. This research aims to improve children's fine motor development. This type of research is Classroom Action Research (PTK). The subjects of this research were group B children, which consisted of 10 Integrated PAUD children at Augrah Sungai Lingkitang, Sangir District, South Solok Regency. This research was carried out in two cycles, each with two meetings. The stages in this research are planning, action, observation, and reflection. There was an increase in children's fine motor development from cycle I to cycle II. In cycle I, meeting 1, the increase in children's fine motor development was 53%, and 63% in meeting 2. In cycle II, meeting 1, the increase in children's fine motor development was 93%, and 97% in meeting 2. Classroom Action Research using meronce activities was successful. Learning using repetitive activities can also train students' fine motor development well.